(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The financial health of several District central co-operative banks (DCCBs) in India is examined in this study using the CAMELS framework, which evaluates Capital sufficiency, Asset quality, Managerial effectiveness, Earnings, Liquidity and Sensitivity to market risk. The study establishes the relationships and distinctions between the CAMELS components and the bank’s total performance using statistical tests including Chi-square, ANOVA, and Regression analysis. Data for the years 2023–2024, collected from official sources such as RBI databases, NABARD records, and publicly available annual reports. The findings show that the efficiency of management and the quality of assets vary significantly among the institutions. Overall financial success is strongly predicted by asset quality and earnings capacity, according to regression analysis. In order to boost competitiveness and sustainability, the report suggests enhancing operational efficiency, lowering nonperforming assets, and increasing governance.